Management Accounting. - Arora, M. N. (Himalaya Pub. House, 2009)
The book has been divided into five chapters to fully cover the syllabus of BMS of Mumbai University. Based on the conviction that students can really learn management accounting by solving problems, the theory and problems approach has been adopted to fully meet all the examination needs of the students in one book. Thus apart from well organized theory, the book has sufficient number of solved problems and illustrations and unsolved problems with answers and hints, apart from objective type questions and essay type questions. This will help students tackle examination questions with ease. Th.